Character of crystallization particle in bitten transfer pump. (July 2018) - Fu, B H; Liu, D; Sun, S L; Zhang, Y L
Abstract: In order to understand the flow pattern of salt-out particles in a bittern transfer pump, the population balance model (PBM) coupled with mixture two-phase was applied to calculate the particle flow. User-defined particle growth and nucleation models were used in this study to consider the actual dynamic behavior of the crystallization particle, such as particle growth, nucleation, aggregation and breakage. The result shows that the average particle size is smaller and more evenly distributed among area of the impeller inlet. The size of crystal particles is different at different regions in the impeller passages with the characteristics of small crystal particles near suction side and large crystal particles near pressure side. In addition, the distribution of average particle size near pressure and suction side has an upward trend from inlet to outlet. The distribution of crystal particles on the blade near the tongue is different from other blades whether it is in the pressure surface or suction surface.